2004
DOI: 10.1073/pnas.0400745101
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of transposition targets in Escherichia coli : The impact of transcription

Abstract: Transposable elements have influenced the genetic and physical composition of all modern organisms. Defining how different transposons select target sites is critical for understanding the biochemical mechanism of this type of recombination and the impact of mobile genes on chromosome structure and function. Phage Mu replicates in Gram-negative bacteria using an extremely efficient transposition reaction. Replicated copies are excised from the chromosome and packaged into virus particles. Each viral genome plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…Previous reports indicate that Mu frequently inserts into highly preferred sites within a target gene (6,13,20). Using DNA microarray analysis, we recently demonstrated that Mu exhibits a 1,000-fold bias in Escherichia coli at the whole-gene level (12). Transcription plays a dominant role in causing this bias.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Previous reports indicate that Mu frequently inserts into highly preferred sites within a target gene (6,13,20). Using DNA microarray analysis, we recently demonstrated that Mu exhibits a 1,000-fold bias in Escherichia coli at the whole-gene level (12). Transcription plays a dominant role in causing this bias.…”
mentioning
confidence: 83%
“…Phage DNA was purified as described previously (12). Mu-host DNA junctions were cloned by selection for Kan resistance.…”
mentioning
confidence: 99%
“…Furthermore, investigations using this technology have largely focused on viral infections in animals and, to a lesser extent, in plants (21,30,35) or fungi (2, 3). Microarrays have been employed to detect phage-specific transcripts in infected cells (11,19), changes in the host genome (14,20), and changes in the transcriptional profiles of bacteria parasitized by lysogenic phages (7). However, to our knowledge, only two studies of virusinduced changes in host gene expression span the entire host genome.…”
mentioning
confidence: 99%
“…It remains unclear why particular regions of the DNA are preferred target sites for Mu transposition under our reaction conditions. Perhaps, as has been suggested, the local structure of the DNA has important influence in determining the location of Mu targeting (38).…”
Section: Fusion Proteins Target Transposition To Dna Near the Arc Opementioning
confidence: 91%